AIDS and religious practice in Africa - Becker, Felicitas, 1971-; Geissler, Wenzel. (Studies of Religion in Africa, 2009)
This volume explores how AIDS is understood, confronted and lived with through religious ideas and practices, and how these, in turn, are reinterpreted and changed by the experience of AIDS. Examining the social production, and productivity, of AIDS - linking bodily and spiritual experiences, and religious, medical, political and economic discourses - the papers counter simplified notions of causal effects of AIDS on religion (or vice versa). Instead, they display people's resourcefulness in their struggle to move ahead in spite of adversity. This relativises the vision of doom widely associated with the African AIDS epidemic; and it allows to see AIDS, instead of a singular event, as the culmination of a century-long process of changing livelihoods, bodily well-being and spiritual imaginaries.